2016
DOI: 10.1186/s12864-016-3316-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic signatures of Mannheimia haemolytica that associate with the lungs of cattle with respiratory disease, an integrative conjugative element, and antibiotic resistance genes

Abstract: Background Mannheimia haemolytica typically resides in cattle as a commensal member of the upper respiratory tract microbiome. However, some strains can invade their lungs and cause respiratory disease and death, including those with multi-drug resistance. A nucleotide polymorphism typing system was developed for M. haemolytica from the genome sequences of 1133 North American isolates, and used to identify genetic differences between isolates from the lungs and upper respiratory tract of cattle with and withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 48 publications
6
58
0
Order By: Relevance
“…; Clawson et al . ) which may reduce the efficacy of current antimicrobials used to treat BRD. Novel methods to mitigate BRD‐related pathogenic bacteria are therefore needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Clawson et al . ) which may reduce the efficacy of current antimicrobials used to treat BRD. Novel methods to mitigate BRD‐related pathogenic bacteria are therefore needed.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment and control of BRD in the beef sector are aimed mainly at bacterial pathogens, through use of antimicrobials. However, studies have shown that antimicrobial resistance in BRD pathogens has increased (Portis et al 2012) and multiresistance has been identified on mobile elements (Klima et al 2014;Clawson et al 2016) which may reduce the efficacy of current antimicrobials used to treat BRD. Novel methods to mitigate BRD-related pathogenic bacteria are therefore needed.…”
Section: Introductionmentioning
confidence: 99%
“…Primers and probes were designed using Geneious 8.1.9 (Biomatters Ltd., Newark, NJ, USA) and verified using the NCBI BLAST nucleotide collection (nt/rt) reference sequence database ( Table 2 (Figure 1). While ICEs differ among strains, the presence of tet(H) (conferring tetracycline resistance) was found in 100% of AMR M. haemolytica strains associated with BRD (12). While the tet(H) gene itself is prevalent among genomes of numerous bacterial species, within ICE, tet(H) is located adjacent to a transposase (tnpA) with a conserved sequence among ICE-containing strains of M. haemolytica, P. multocida, and H. somni.…”
Section: Primer and Probe Designmentioning
confidence: 99%
“…Excluding M. bovis, the genomes of BRD pathogens often contain integrative conjugative elements (ICE), mobile genetic elements that can harbor multiple AMR genes and encode the conjugation machinery required for transfer of ICE between BRD pathogens and to other bacteria (4,9). The resulting multi-drug resistance (MDR) among some BRD pathogens containing ICE presents a significant challenge for the efficacy of antimicrobial therapy as a treatment for BRDClawson et al (12) found that the gene tet(H), which confers tetracycline resistance was present in all AMR M. haemolytica strains isolated from confirmed BRD cases, and was also frequently found in P. multocida (13) and H. somni ICE (14). Furthermore, tet(H) was adjacent to the transposase gene tnpA, a core ICE gene associated with increased minimum inhibitory antimicrobial concentrations in M. haemolytica, H. somni, and P. multocida (15).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the lktD locus of 1,133 M. haemolytica isolates sequenced in a previous study was used for screening of potential polymorphisms at the primerbinding sites. 4 Primers and probe sequences were selected that were unique and did not possess significant identity to other sequences in GenBank, with the exception of M. haemolytica (Table 2). M. haemolytica had some sequence identity with closely related species; however, some polymorphisms were present in primer and probe-binding sites for non-target species ( Supplementary Fig.…”
Section: Real-time Pcr Assay Designmentioning
confidence: 99%